The effect of the Baduanjin for the elderly based on the meridian theory combined with the Intelligent Elderly Comprehensive Assessment on the cognitive function of patients with early-stage Alzheimer's disease (基于经络学说的老年八段锦结合"智慧老年综合评估"对阿尔茨海默病早期患者认知功能的影响) - CHENG Yao (程瑶); TAN Zihu (谭子虎); CAI Yazheng (蔡亚峥) (Journal of International Translational Medicine Limited, 2021)
Objective To observe the effect of the Baduaniin for the elderly based on the meridian theory combined with the Intelligent Elderly Comprehensive Assessment on the cognitive function of patients with early-stage Alzheimer's disease. Methods Using the Intelligent Elderly Comprehensive Assessment system, 40 patients with early early-stage Alzheimer's disease were assessed. All patients received comprehensive treatment and nursing management, and modified Baduanjin exercise for 6 months was carried out. Before and after the intervention, the patients were assessed by the "Intelligent Elderly Comprehensive Assessment" system, and take a blood sample to detect blood lipids, serum interleukin-6 (IL-6), acetylcholine (Ach) and malondialdehyde (MDA). Results Six months later, the total score of Mini-Mental State Examination (MMSE) and factor scores of Montreal Cognitive Assessment Scale (MoCA) were higher than those before intervention, with significant differences(P<0. 05). The serum total cholesterol, IL-6 and MDA levels were decreased after intervention (P<0. 05), and the level of HDL was increased after intervention (P<0. 01). Conclusion Based on the theory of meridian, the Baduanjin exercise combined with the Intelligent Elderly Comprehensive Assessment can improve the cognitive function of the patients with early-stage Alzheimer's disease, and has the effects of lowering blood lipids, anti-oxidation and anti-inflammatory. (目的 观察基于经络学说的老年八段锦结合"智慧老年综合评估"对阿尔茨海默病早期患者认知功能的影响。方法 利用 "智慧老年综合评估"系统对住院患者进行评估和筛选, 确定阿尔茨海默病早期患者40例。在基础治疗的基础上, 实施老年八段锦干预, 干预时间为6个月。干预前后分别采用"智慧老年综合评估"系统对患者进行综合评估, 并抽血检测血脂、血清白细胞介素-6(IL-6)、丙二醛(MDA)。结果 干预6个月后, 患者简易智力状态检查(MMSE)总分和蒙特利尔认知量表(MoCA)中的视空间与执行功能、延迟回忆、定向力评分均较干预前提高, 差异有统计学意义(P＜0. 05)。干预后, 患者血清总胆固醇、IL-6和MDA水平低于干预前(P<0. 05), 高密度脂蛋白胆固醇水平高于干预前(P＜0. 01)。结论 基于经络学说的老年八段锦结合"智慧老年综合评估"能改善阿尔茨海默病早期患者的认知功能, 并有降血脂、抗氧化和抗炎作用。)